Pedigree vs. Grit : predicting mutual fund manager performance - Eso?, Peter; Schmedders, Karl; Hunter, Graeme (London : SAGE Publications Ltd, 2017)
An asset management company must replace the manager of its two signature mutual funds, who is about to retire. Two candidates have been short-listed. The management team is divided and cannot decide which of the two candidates would make the better mutual fund manager. The retiring manager presents a linear regression model to examine success factors of mutual fund managers. This linear regression is the starting point for the subsequent analysis.
Originally published: Eso, P., Schmedders, K., & Hunter, G. (2007). Pedigree vs. grit: Predicting mutual fund manager performance. 5-407-755. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mutual funds -- Management -- United States -- Case studies; Asset-liability management -- United States -- Case studies